The Thyroid Hormone Receptors Inhibit Hepatic Interleukin-6 Signaling During Endotoxemia - Contreras Jurado, Silvia Constanza; Alonso Merino, Elvira; Saiz Ladera, Cristina; Valiño, Arturo José; Regadera, Javier; Alemany, Susana; Aranda, Ana (My University, 2021)
Decreased thyroidal hormone production is found during lipopolysaccharide (LPS)-induced endotoxic shock in animals as well as in critically ill patients. Here we studied the role of the thyroid hormone receptors (TRs) in activation of STAT3, NF-¿B and ERK, which play a key role in the response to inflammatory cytokines during sepsis. TR knockout mice showed down-regulation of hepatic inflammatory mediators, including interleukin 6 (IL-6) in response to LPS. Paradoxically, STAT3 and ERK activity were higher, suggesting that TRs could act as endogenous repressors of these pathways. Furthermore, hyperthyroidism increased cytokine production and mortality in response to LPS, despite decreasing hepatic STAT3 and ERK activity. This suggested that TRs could directly repress the response of the cells to inflammatory mediators. Indeed, we found that the thyroid hormone T3 suppresses IL-6 signalling in macrophages and hepatocarcinoma cells, inhibiting STAT3 activation. Consequently, the hormone strongly antagonizes IL-6-stimulated gene transcription, reducing STAT3 recruitment and histone acetylation at IL-6 target promoters. In conclusion, TRs are potent regulators of inflammatory responses and immune homeostasis during sepsis. Reduced responses to IL-6 should serve as a negative feedback mechanism for preventing deleterious effects of excessive hormone signaling during infections.